The quality of preoperative diagnostics and surgery and their impact on delays in breast cancer treatment – A population based study. (April 2016) - Ojala, Kaisu; Meretoja, Tuomo J.; Mattson, Johanna; Salminen-Peltola, Päivi; Leutola, Suvi; Berggren, Marianne; Leidenius, Marjut H.K.
Abstract: Background and objectives: This study aims to clarify quality of breast cancer surgery in population-based setting. We aim to elucidate factors influencing waiting periods, and to evaluate the effect of hospital volume on surgical treatment policies. Special interest was given to diagnostic and surgical processes and their impact on waiting times. Methods: All 1307 patients having primary breast cancer surgery at the Helsinki and Uusimaa Hospital District during 2010 were included in this retrospective study. Results: Median waiting time for primary surgery was 24 days and significantly affected by additional imaging and diagnostic biopsies as well as hospital volume. Final rate of breast conserving surgery was surprisingly low, 51%, not affected by hospital volume, p = 0.781. Oncoplastic resection and immediate breast reconstruction (IBR) were performed more often in high volume units, p < 0.001. Quality of axillary surgery varied with unit size. Multiple operations, IBR and high volume unit were factors prolonging initiation of adjuvant treatment. Conclusion: Quality of preoperative diagnostics play a crucial role in minimizing the need of repeated imaging and biopsies as well as multiple operations. Positive impact of high-volume hospitals becomes evident when analyzing procedures requiring advanced surgical techniques. High-volume hospitals achieved better quality in axillary surgery. Highlights: The factors influencing waiting periods and the effect of hospital volume on breast cancer treatment were investigated in population-based setting. Quality of preoperative diagnostics plays a crucial role in minimizing the need of repeated imaging and biopsies as well as multiple operations. Positive impact of high-volume hospitals becomes evident when analyzing procedures requiring advanced surgical techniques. High-volume hospitals achieved better quality in axillary surgery.